NLRP6 Inflammasome Regulates Colonic Microbial Ecology and Risk for Colitis - Elinav, Eran; Strowig, Till; Kau, Andrew L.; Henao-Mejia, Jorge; Thaiss, Christoph A.; Booth, Carmen J.; Peaper, David R.; Bertin, John; Eisenbarth, Stephanie C.; Gordon, Jeffrey I.; Flavell, Richard A. (Cell, 2011)
Inflammasomes are multiprotein complexes that function as sensors of endogenous or exogenous damage-associated molecular patterns. Here, we show that deficiency of NLRP6 in mouse colonic epithelial cells results in reduced IL-18 levels and altered fecal microbiota characterized by expanded representation of the bacterial phyla Bacteroidetes ( Prevotellaceae) and TM7. NLRP6 inflammasome-deficient mice were characterized by spontaneous intestinal hyperplasia, inflammatory cell recruitment, and exacerbation of chemical colitis induced by exposure to dextran sodium sulfate (DSS). Cross-fostering and cohousing experiments revealed that the colitogenic activity of this microbiota is transferable to neonatal or adult wild-type mice, leading to exacerbation of DSS colitis via induction of the cytokine, CCL5. Antibiotic treatment and electron microscopy studies further supported the role of Prevotellaceae as a key representative of this microbiota-associated phenotype. Altogether, perturbations in this inflammasome pathway, including NLRP6, ASC, caspase-1, and IL-18, may constitute a predisposing or initiating event in some cases of human IBD. [Display omitted] [Display omitted] ► NLRP6 inflammasome in colonic epithelium regulates gut microflora ► NLRP6 −/− mice exhibit dysbiosis, with expansion of Prevotellaceae and TM7 ► Dysbiosis results in transmissible autoinflammation ► Microflora-induced inflammation is caused by epithelial CCL5 induction